Lipase-catalyzed preparation of galactose oleate ester in ionic liquid - Mohd Saupi, Hanim Salami (2012)
Lipase-catalyzed preparation of galactose oleate ester was performed in 1-butyl-3-methylimidazolium tetrafluoroborate ([Bmim][BF4]) ionic liquid with the addition of dimethylsulfoxide (DMSO) as a solubilizing agent and co-solvent, and Lipozyme RM IM (lipase from Rhizomucor miehei immobilized on macroporous anion exchange resin) as the biocatalyst. Galactose oleate ester was purified and characterized by thin layer chromatography (TLC), fourier transform-infrared spectroscopy (FT-IR), high performance liquid chromatography (HPLC), direct injection-mass spectrometry (DI-MS), liquid chromatography-mass spectrometry (LC-MS) and nuclear magnetic resonance (NMR). Optimal preparation conditions with a high conversion rate (87%) was obtained in DMSO:[Bmim][BF4] (1:20, v:v) with 2% (w/w) Lipozyme RM IM loaded for 2 h, at 60C, with a stirring speed of 300 rpm and a molar ratio of galactose to oleic acid of 1:3. The formation of galactose oleate ester was evaluated through kinetic study using Michaelis-Menten kinetic model. The Ping-Pong Bi-Bi mechanism with one substrate inhibition was adopted as it best explained the experimental findings. The kinetic results showed the Km values (galactose = 0.02905 mmol/mL.mg and oleic acid = 0.00025 mmol/mL.mg). The low Michaelis constant values showed that the Lipozyme RM IM has higher affinity towards both substrates. The overall results on the physicochemical studies such as hydrophile lipophile balance (HLB) value, physical state, refractive index and surface tension illustrated that the ester possess suitability for industrial application as emulsifiers and surfactant.